Enzyme immobilization on magnetic nanoparticles for polymer synthesis - Papatola Francesco; Slimani Sawssen; Davide Peddis; Alessandro Pellis (2024)
To satisfy the increasing request for environmentally friendly polymers, in line with the “European green deal”1, the ability of enzymes to transform natural and non-natural compounds into polymers is considered as an environmentally friendly alternative to the traditional chemical synthetic pathways2. Improving enzyme’s activity and stability as well as preserving selectivity is a must and can be achieved by immobilizing the biocatalyst on the surface of metal oxide nanoparticles3. The aim of this work is to design a smart platform consisting of spinel iron oxides (MeFe2O4; Me: Fe2+ and Co2+) nanoparticles (i.e., single magnetic nanoparticles, ordered aggregates of nanoparticles) with optimized morpho structural (i.e., particles size, shape and crystallinity), textural (i.e., high surface area) and magnetic properties. Candida antarctica lipase B (CaLB) was immobilized on nanoparticles’ surface investigating the optimal bioconjugation conditions. Once immobilized on magnetic nanoparticles surface, CaLB was tested for enzymatic polymerization reaction to synthetize polyesters starting from renewable monomers such as adipic acid and 1,8-octanediol. The percentage of conversion of substrate monomers was studied by Nuclear Magnetic Resonance analysis (NMR), and the molecular weights of the polyester products were analyzed by gel permeation chromatography (GPC). As final step, enzyme recyclability over several cycles of condensation reaction was tested.